Dynamic tracing of fecal bacteria processes from a river basin to an estuary using a 2D/3D model. Issue 2 (11th December 2022) - Huang, Guoxian; Falconer, Roger; Lin, Binliang; Xu, Chenghui
Abstract: In this study fecal bacteria processes have been investigated using the EFDC 2D/3D model, based on local refinements using an orthogonal curvilinear grid system and with the model being applied to Ribble river basin, through the estuary, and into the Fylde Coast. The input fluxes from numerous minor rivers and streams within the basin were solved using a grid‐based distributed hydrological model (GDHM) and a river network 1D model (RNM1D), developed by the authors. The detailed measured hydrodynamic data, included tide levels and nearshore ADCP 3D velocity field data at four sites and with data being recorded over a 2‐week period. During this period continuous monitoring using four types of tracers was also undertaken across the Ribble basin, which included sampling for E. coli ( EC ) and Intestinal Enterococci (IE) parameters. Monitoring devices, in the form of buoys, were also used and moved with currents, driven by upstream discharges, tides, waves and wind. The results showed: (i) the grid system gave a detailed topographical representation of the transition zones from the river system to the estuary and coast, with the hydrodynamic and related solute transport processes being well represented; and (ii) the model predicted results fit generally well with the water stage, 3D flow velocity profiles (with some errors in the bottom and surface layers), and E. coli concentrations. The tracer paths from the injection sites were simulated using a Lagrangian particle tracking method, which showed that the tracer from the north bank outfalls and the Ribble river could propagate to the highly popular bathing beaches at Blackpool, particularly under the action of South Westerly winds. More detailed solutions and refinements (e.g., wave driven by the wind and density flows caused by different salinities, temperatures, and suspended sediment concentrations) need to be considered in the next stage of this study.